Predictive factors of the attack efficacy: the case of the Brazilian women's Volleyball League champion team - Augusto César Rodrigues Rocha; Auro Barreiros Freire; Leonardo Rodrigues Martins; Mariana Pereira Maia; Juracy da Silva Guimarães; Herbert Ugrinowitsch; Henrique de Oliveira Castro; Gustavo De Conti Teixeira Costa (Universidade Federal de Santa Catarina, 2019)
The aim was to identify the predictive factors of the attack efficacy of the Brazilian women's League Champion team according to the level of performance of the opposing team. The sample was composed of the observation of 1137 attacks in 21 games of the 2015-2016 Brazilian women's Volleyball League champion team. The results were significant to identify the predictive factors of the attack efficacy against high (x2=110.562; p<0.00001), intermediate (x2=64.134; p<0.00001) and low (x2=62.137; p<0.00001) performance opponents. Thus, it is concluded that when playing against high- performance teams, powerful attack for position 6 and second attack tempo increase the chances of attack point; powerful attacks for position 1 and 5 reduce the chances of game continuation; and powerful attack for position 6 increases the chances of blocking. In addition, in games against intermediate-performance teams, reception that allows organized attack without all attack options reduces the chances of attack point and game continuation, while the reception effect did not seem to be a predictive factor of the attack efficacy in games against high- and low-performance opponents and, finally, in games against low-performance teams, powerful attack for position 1 reduces the chances of game continuation and attack blocking.